Wasiat Wajibah sebagai Instrumen Perlindungan Hak Ahli Waris Beda Agama: Studi Komparatif Indonesia dan Negara-Negara Muslim dalam Perspektif Keadilan Hukum - Nadya Artika Maulani; Abd. Rouf (AHKAM, 2026)
Religious difference is one of the impediments to inheritance in Islamic law, which causes non-Muslim heirs not to obtain inheritance rights from Muslim testators. In its development, a number of Muslim countries have developed the concept of wasiat wajibah as a legal protection instrument for parties who are barred from receiving inheritance. This study aims to analyze the regulation of wasiat wajibah for heirs of different religions in Indonesia and Muslim countries, identify its similarities and differences, and examine its relevance from the perspective of legal justice. This study is normative legal research using statutory, conceptual, and comparative approaches. The results show that Indonesia provides protection for heirs of different religions through the development of the concept of wasiat wajibah based on Supreme Court jurisprudence. Conversely, Egypt and Morocco continue to maintain the prohibition on inheritance between different religions and do not expand the application of wasiat wajibah to non-Muslim heirs, but provide a bequest mechanism as a means of transferring assets to parties who are barred from inheriting. From the perspective of legal justice, these differences indicate variations in approaches to protecting the economic interests of family members without eliminating the basic principles of Islamic inheritance. The conclusion of this study affirms that wasiat wajibah can function as a legal protection instrument for heirs of different religions without negating the principle prohibiting inheritance between different religions in Islamic law. These findings contribute to the development of Islamic inheritance law reform that is more responsive to the dynamics of plural society.